A novel peptide-based recognition probe for the sensitive detection of CD44 on breast cancer stem cells. Issue 6 (December 2015) - Cho, Jun-Haeng; Lee, Sang-Choon; Ha, Na-Reum; Lee, Su-Jae; Yoon, Moon-Young
Abstract: Metastasis and recurrence of breast cancer remain significant clinical problems. The expression level of CD44 protein is higher in breast cancer-initiating cancer stem cells; therefore, the early detection of CD44 using a sensitive diagnostic probe is important for breast cancer diagnosis and therapeutic purposes. In this study, we fabricated a polyvalent directed peptide polymer (PDPP) that specifically recognized the CD44 biomarker, as confirmed by immunocytochemistry tests and fluorescence-activated cell sorting assessment. Our results indicate that PDPP is useful as a novel tool for the sensitive detection of breast cancer stem cells. Highlights: A novel PDPP was designed to sensitive detection of CD44 on breast cancer stem cell. The binding properties of PDPP was optimized in combinational synthetic conditions. The PDPP shown novel binding affinity and sensitivity to CD44 in cellular level.